A multi-country study using MALDI-TOF mass spectrometry for rapid identification of Burkholderia pseudomallei - Watthanaworawit, W; Roberts, T; Hopkins, J; Gassiep, I; Norton, R; Robinson, MT; Silisouk, J; Sar, P; Sao, S; Amornchai, P; Limmathurotsakul, D; Wuthiekanun, V; et al. (BioMed Central, 2021)
Background Burkholderia pseudomallei is the bacterial causative agent of melioidosis, a difficult disease to diagnose clinically with high mortality if not appropriately treated. Definitive diagnosis requires isolation and identification of the organism. With the increased adoption of MALDI-TOF MS for the identification of bacteria, we established a method for rapid identification of B. pseudomallei using the Vitek MS, a system that does not currently have B. pseudomallei in its in-vitro diagnostic database.